Utilization of fine needle aspiration cytology at Kamuzu central hospital. - Shiraz Khan; George Liomba; Nora E Rosenberg; Christopher Stanley; Cocxilly Kampani; Bal Mukunda Dhungel; Mina C Hosseinipour (PLoS ONE)
Background Fine needle aspiration cytology (FNAC) has been widely accepted to be a safe, accurate, prompt and inexpensive procedure for diagnosis of both neoplastic and infectious diseases in adult and pediatric populations. Despite its value for diagnosis, FNAC is underutilized in resource limited countries. We reviewed the utilization of FNAC after it was introduced at Kamuzu Central Hospital (KCH). Methods A retrospective review of all FNAC performed at KCH laboratory during the period of January 2012 to July 2014 was conducted using an electronic database from KCH laboratory. We evaluated factors associated with a diagnostic sample using multivariate logistic regression model. Results 750 FNAC were reviewed from 722 patients: 56.9% were adults >15 years and 54% were female. The number of FNAC increased annually from 56 (2012) to 379 (2013) to 315 (up to July 2014). Of 750 FNAC, 56.4% were performed by non-pathologists. The most common sites were lymph nodes (38.1%), abdomen (25.8%), breast (16.3%), and head & neck (15.7%). Most of the samples (77.6%) were diagnostic. FNAC was more likely to be diagnostic if performed by pathologists versus non-pathologists (OR 1.78, 95% CI 1.20-2.64), in 2013 compared to 2012 (OR 1.95, 95% CI 1.05-3.56), or performed on a deep lesion versus a subcutaneous lesion (OR 1.71, 95% CI 1.15-2.5), or if samples were taken from the head and neck (OR 2.4, 95% CI: 1.39-4.39), and abdomen (OR 2.66, 95%CI1.59-4.42) compared to those from the lymph nodes. The odds of a diagnostic test did not differ significantly according to gender, HIV status, or age groups. Conclusion Most FNACs successfully diagnosed the presence or absence of disease, with substantial improvements over time. However, training for non-pathologists may facilitate more diagnostic results.